STRATEGI KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN MOTIVASI KERJA GURU - Helsi Helsi Febrianti; Umy Nadrah Simatupang; Nurhizrah Gistituati (Jurnal Dedikasi Pendidikan, 2023)
Leadership is the competence of an individual to be able to influence others. School is a place that works on the development of personality characteristics of human resources. The teacher's role is very important, so the principal's work in order to improve teacher performance by motivating teachers must be as effective and efficient as possible. The aim of the authors of this article is to examine leadership strategies that school principals can use to increase teacher motivation. The method used is the literary method which follows various literary studies using various reading sources, both books and journals. Based on the results of studies from various sources, it can be understood that the principal's management strategy to increase teacher work motivation is important, because the right motivation of the principal to teachers can influence motivation. quality of work and teacher commitment. A teacher's work motivation is influenced by two factors, namely internal factors and factors that come from outside the teacher.